Effect of Probiotics on Liver Enzymes in Patients With Non-alcoholic Fatty Liver Disease: An Umbrella of Systematic Review and Meta-Analysis - Musazadeh, Vali; Roshanravan, Neda; Dehghan, Parvin; Ahrabi, Sana Sedgh (Frontiers in Nutrition, 2022)
Nonalcoholic fatty liver disease (NAFLD) has become prevalent in recent decades, especially in developed countries; yet the approaches for preventing and treating NAFLD are not clear. This study aimed to summarize meta-analyses of randomized controlled trials that examined the effects of probiotics on NAFLD. We systematically searched PubMed, Scopus, Embase, Web of Science, and Cochrane Central Library databases up to August 2021. All Meta-analysis studies assessing the effect of probiotics on liver function tests [alanine aminotransferase (ALT), aspartate aminotransferase (AST), and Gamma-glutamyl transferase (GGT)] were included. Meta-analysis was conducted using a random-effects model. Sensitivity and subgroup analyses were also performed. The umbrella study covered ten eligible studies involving 5,162 individuals. Beneficial effects of probiotics supplementation were revealed on ALT (ES= -10.54 IU/L ; 95% CI:-12.70, -8.39; p< 0.001; I2 = 60.9%, p= 0.006), AST (ES= -10.19 IU/L, 95%CI: -13.08, -7.29, p<0.001; I2 =79.8 %, p<0.001), and GGT ( ES= -5.88 IU/L, 95% CI: -7.09, -4.67, p= 0.009; I2 =0.0 %, p = 0.591) levels. Probiotics have ameliorating effects on ALT, AST, and GGT levels in patients with NAFLD. Overall, Probiotics could be recommended as an adjuvant therapeutic method for the management of NAFLD.